P44. Facial onset sensory motor neuronopathy (FOSMN) syndrome – Evidence for an oligogenic entity, though no evidence of a genetic link to ALS. Issue 8 (August 2015) - Prudlo, J.; Bürmann, J.; Weis, J.; Biskup, S.; Krüger, S.; Dillmann, U.
<x xml:space="preserve">Abstract</x> Facial onset sensory motor neuronopathy (FOSMN) syndrome is a rare sporadic entity which has only recently been described (Vucic et al., 2006). It is presumed to be neurodegenerative; its etiology however, remains unknown. Despite initial facial sensory symptoms, FOSMN syndrome has been linked to amyotrophic lateral sclerosis (ALS), a link which has recently been underpinned by a description of a D90A superoxide dismutase-1 (SOD-1) mutation in a case of FOSMN syndrome (Dalla Bella et al., 2014). We describe another case of a presumed FOSMN syndrome in a 70-year-old man. At the age of 56, the patient experienced facial and bulbar motor symptoms, though without prominent trigeminal sensory symptoms. He developed slow progressive mild dysarthria, dysphagia, and hoarseness, showing pronounced facial weakness, fasciculation, and myokymia, wasted furrowed tongue, but no upper or lower limb weakness or fasciculation or no upper motor neuron signs. Electrodiagnostic findings revealed an abnormal blink reflex, masseter reflex, masseteric silent period, and trigeminal SEPs. Nerve conduction studies showed a sensory-motor polyneuropathy predominantly demyelinating. A chronic neuropathy with predominant remyelination and regeneration, though without cellular infiltration or amyloid deposition, could be observed in a sural nerve biopsy. A pathologic trinucleotide CAG repeat expansion in the androgen receptor gene (spinal and bulbar muscular atrophy, Kennedy's disease) and a dynactin mutation were excluded by means of Sanger sequencing. Additionally, next-generation sequencing targeted to 242 neurodegeneration associated genes revealed a homozygous variant in the CYP2U1 gene (c.992A>G, p.N331S) and a heterozygous variant in the SYNE1 gene (c.6268G>C, p.E2090Q). These variants have yet to be described in genetic databases. No mutations could be detected among 26 screened ALS-related genes. Mutations in CYP2U1 can cause autosomal recessive inherited spastic paraplegia type 56 (SPG 56). Mutations in SYNE1 can cause either autosomal dominant Emery-Dreifuss muscular dystrophy-4 (EDMD4) or autosomal recessive spinocerebellar ataxia type 8 (SCAR8). The relationship between the CYP2U1 and SYNE1 variants and FOSMN syndrome established here requires further investigation. The genetic data presented showed no link between FOSMN syndrome and ALS, instead pointing towards evidence of an oligogenic basis for FOSMN syndrome.